Determinants of Firm Value in The Mining Sector: The Role of Profitability, Capital Structure, and Liquidity - Sephia Angela Yosephine; Liana Susanto (PT Publikasiku Academic Solution, 2026)
Determinants of Firm Value in The Mining Sector: The Role of Profitability, Capital Structure, and Liquidity” This study aims to analyze the effects of profitability, capital structure, and liquidity on firm value in mining sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. Firm value is proxied by Price-to-Book Value (PBV), profitability is proxied by Return on Assets (ROA), capital structure is proxied by Debt-to-Equity Ratio (DER), and liquidity is proxied by Current Ratio (CR). This research applies a quantitative approach using secondary data obtained from the companies’ annual financial statements. The sample was selected using a purposive sampling method based on predetermined criteria, resulting in 11 companies with a total of 55 observations after excluding outliers. The data were analyzed using panel data regression with the assistance of EViews 13. The results show that profitability has a positive and significant effect on firm value. Meanwhile, capital structure and liquidity have no significant effect on firm value. These findings indicate that a company’s ability to generate profits is a more important consideration for investors than its level of debt usage or its ability to meet short-term obligations. Therefore, mining sector companies are expected to improve profitability through effective and efficient asset management in order to increase firm value.